Integrated gut/liver microphysiological systems elucidates inflammatory inter‐tissue crosstalk - Chen, Wen L.K. (Biotechnol Bioeng, 2017)
A capability for analyzing complex cellular communication among tissues is important in drug discovery and development, and in vitro technologies for doing so are required for human applications. A prominent instance is communication between the gut and the liver, whereby perturbations of one tissue can influence behavior of the other. Here, we present a study on human gut‐liver tissue interactions under normal and inflammatory contexts, via an integrative multi‐organ platform comprising human liver (hepatocytes and Kupffer cells), and intestinal (enterocytes, goblet cells, and dendritic cells) models. Our results demonstrated long‐term (>2 weeks) maintenance of intestinal (e.g., barrier integrity) and hepatic (e.g., albumin) functions in baseline interaction. Gene expression data comparing liver in interaction with gut, versus isolation, revealed modulation of bile acid metabolism. Intestinal FGF19 secretion and associated inhibition of hepatic CYP7A1 expression provided evidence of physiologically relevant gut‐liver crosstalk. Moreover, significant non‐linear modulation of cytokine responses was observed under inflammatory gut‐liver interaction; for example, production of CXCR3 ligands (CXCL9,10,11) was synergistically enhanced. RNA‐seq analysis revealed significant upregulation of IFNα/β/γ signaling during inflammatory gut‐liver crosstalk, with these pathways implicated in the synergistic CXCR3 chemokine production. Exacerbated inflammatory response in gut‐liver interaction also negatively affected tissue‐specific functions (e.g., liver metabolism). These findings illustrate how an integrated multi‐tissue platform can generate insights useful for understanding complex pathophysiological processes such as inflammatory organ crosstalk. Biotechnol. Bioeng. 2017;114: 2648–2659. © 2017 Wiley Periodicals, Inc.